An Overview on Use of Biosensor in Agriculture (International Journal of Innovative Research in Engineering & Management, 2021)
The biosensor are the analytical instrument that transforms biological reactions into electrical signals. They include  tissue-based enzyme-based, DNA biosensors, immune sensors, piezoelectric, thermal, and biosensors. Biosensors  may be utilized in a number of agricultural applications, such  as assessing toxins in soils and crops, detecting and  diagnosing infectious illness in crops and animals, on-line  monitoring of key food process parameters, measuring animal  reproduction, and screening for veterinary drugs. This article  investigates biosensors, their kinds, and their applications.  This paper also discusses agriculture and the application of  biosensors in agriculture, among other topics. To make cell  and tissue-based biosensors, genetically engineered proteins  are injected into cells ex vivo or in vivo. They allow the  researcher to constantly and noninvasively detect levels of  hormones, medicines, or poisons using bio photonics or other  physical principles. In this regard, the spectrum may be useful  in the field of aging research in the future.
Keywords: Agriculture; Biosensor; Enzyme; Sensor; Tissue